Zastosowanie lasera diodowego w leczeniu retinopatii wcześniaków – wyniki rocznej obserwacji - Kobylarz, Joanna; Piwowarczyk, Anna; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: To evaluate structural and functional outcomes in one-year old patients, treated for retinopathy of prematurity (ROP) with transpupillary diode laser photocoagulation. Materials and methods: 58 children (116 eyes) 12 months old, after treatment for ROP with diode laser photocoagulation, were examined. Both, functional outcome (visual acuity – basing on the examination with Teller Acuity Card Procedure), and structural outcome were evaluated. The cycloplegic refraction was examined in all cases. Results: We have found good functional outcome in 81.9%, and good structural outcomes in 96.5% of examined eyes. 64.6% of eyes had hyperopic refractive error, and 31% were myopic. Conclusions: Diode laser photocoagulation is an effective method of treatment for ROP.